Dinâmica do forrageio de Constrictotermes Cyphergaster (Blattaria, Isoptera) em um ecossistema semiárido do nordeste brasileiro - Silva, Amanda Cosme da (2017)
Termites present seasonal foraging cycles, influenced mostly by climatic conditions, food availability, annual variations in colony size and the overall rate of resource used in the colony. This study investigated the foraging dynamics of Constrictotermes cyphergaster in the time and space in the Caatinga of Northeast of Brazil, with the objective to evaluate the correlation between the quality and availability of the resources with foraging routes, in addition to energy aspects of the colony to produce nymphs. Eight colonies were monitored during fifteen days in each trimester, from January 2016 to June 2017, totalizing five samplings. The traced routes and food items explored by the termite were demarcated in the area of use of the colonies. Samples of 100 soldiers and 100 workers were collected to access biomass and contents of proteins, lipids, carbohydrates and total sugars. Plant samples of the main exploited resources were collected for analysis of carbon and nitrogen. Seventeen plant species were found to be exploited by C. cyphergaster, among those Croton spp., Mimosa spp. and Poincianella pyramidalis were the most visited and the most abundant species. Foraging trails are likely to be targeted by choosing sites whose resource selection optimize the cost-benefit of the activity, where the availability of the resource within the area of use seems to be more attractive for the termite. The foraging used area showed variation between the seasons. The same was not observed for the duration of the activity and the foraging intensity. Workers and soldiers showed higher protein and lipids concentrations during rainy periods, with an increase in body biomass. In the dry season, carbohydrates and total sugars presented significantly higher differences than rainy season. There was no direct link between nutrition of colony and specific foraging strategies for each climatic period. However, the increase in body biomass during rainy periods may indicate that the quality of the resource is more important for the termite than the quantity consumed.